Perovskite Nanocrystals: Synthesis, Stability, and Optoelectronic Applications. Issue 3 (10th March 2021) - Wang, Shizhe; Yousefi Amin, Amir Abbas; Wu, Linzhong; Cao, Muhan; Zhang, Qiao; Ameri, Tayebeh
Abstract : Perovskite Nanocrystals In article number 2000124, Shizhe Wang, Qiao Zhang, Tayebeh Ameri, and co‐workers summarize the recent development of perovskite nanocrystals. The synthetic methods, stability issues, and encapsulation of these materials are introduced. The precise control of the morphologies and shapes on perovskite nanocrystal via brilliant synthetic strategies is like assembling single crystal units one by one. These materials also possess a great potential to be widely used in optoelectronic applications.